A smartphone‐centric platform for remote health monitoring of heart failure. (14th April 2014) - Bisio, Igor; Lavagetto, Fabio; Marchese, Mario; Sciarrone, Andrea
Summary Heart failure is a chronic disease that alternates intense and weak phases and requires repeated and frequent hospital treatments. The use of automatic instruments for a remote and ubiquitous monitoring of biological parameters relevant to heart failure pathophysiology offers new perspectives to improve the patients' quality of life and the efficacy of the treatment. The platform described in this paper represents an implementation of an automatic remote monitoring tool where smartphones play a crucial role. They are not employed just to communicate through traditional client‐server applications and they are not only the hub of information sent by sensors, but they also act as intelligent processors and autonomous sensors of the patients' motion through a high‐accuracy activity recognition algorithm. The proposed platform combines the evolution of health systems and the consequent needs of modern telemedicine with the current context‐aware capability of recent smartphones, obtained by implementing specific algorithmic solutions, and with the anything, anytime, and anywhere communication capability of the pervasive communications paradigm. Performance evaluation focuses on the accuracy of the activity recognition estimation, on its applicability to real life, and on the data exchange between smartphones and medical server, allowing to envisage the potential of the designed platform. Copyright © 2014 John Wiley & Sons, Ltd.